Analisis Kemampuan Pemecahan Masalah Matematis Ditinjau Dari Self-Confidence Siswa Madrasah Tsanawiyah di Mataram, Indonesia - Khairunnisa, Salsabila; Evendi, Erpin (Mathematic Education Departement, State Islamic University of Mataram, 2023)
Abstract This study aims to describe the ability to solve mathematical problems in terms of the self-confidence of class VIII students at MTs Assalam Mataram. This type of descriptive qualitative research chose 3 research subjects from 22 class VIII students who had high self-confidence, moderate self-confidence, and low self-confidence categories. Data were collected using a self-confidence questionnaire instrument, tests of mathematical problem-solving abilities in circle material, and interviews. Data analysis techniques are carried out by collecting data, presenting data, condensing data, drawing conclusions, and verifying. And checking the validity of the data using credibility, technical triangulation, transferability, dependability, and confirmability. The results of the study were that the high self-confidence category of students was 2.30%, for the test of mathematical problem-solving abilities with high criteria it showed that in general, they were able to fulfill all problem-solving indicators, the medium self-confidence category was 59.6%, for the problem-solving ability test the mathematical criteria were moderate, indicating that they were only able to meet three indicators of problem-solving ability, and the low self-confidence category was 38.1%, for the mathematical problem-solving ability test, the problem-solving ability only met one indicator.